The difference in the ratio of the maxillary anterior teeth mesiodistal to the golden proportion value after class I malocclusion treatment with Edgewise standard fixed appliance - Suherman, Agutina; Mardiati, Endah; Hambali, Tono; Thahar, Bergman (Padjadjaran Journal of Dentistry, 2010)
Introduction: The purpose of this study was to determine the difference in the ratio of maxillary anterior teeth as the results of Edgewise Standard fixed orthodontic treatment with and without extraction with golden proportion values. Methods: This study is using a retrospective analitist descriptive method. Sample divided at two groups of 13 patients with extraction of first premolar and 19 patients without first premolar extraction. The study population was patients who had completed the Edgewise Standard fixed orthodontic treatment at the Orthodontics Specialist Professional Program of the Faculty of Dentistry Universitas Padjadjaran at 2000-2009. The study was conducted using frontal intraoral photometry before and af-ter treatment with 3R photo size, then measured with electronic digital calliper software. Results: Evaluation is done by measuring the maxillary anterior teeth ratio using phimatrix software on frontal intra oral photometry of the post standard edgewise orthodontics patients with Class I malocclusion to the golden proportion, then proceed with statistical t-test. Conclusion: The conclusion of this study shows that the maxillary anterior teeth post standard edgewise orthodontic treatment in class I dento-skeletal patients with or without the first premolar extraction whose treated in orthodontic resident’s clinic Padjadjaran University shows a significant differences with the golden proportion.